2018
DOI: 10.1371/journal.pone.0201298
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism by which water and protein electrostatic interactions control proton transfer at the active site of channelrhodopsin

Abstract: Channelrhodopsins are light-sensitive ion channels whose reaction cycles involve conformation-coupled transfer of protons. Understanding how channelrhodopsins work is important for applications in optogenetics, where light activation of these proteins triggers changes in the transmembrane potential across excitable membranes. A fundamental open question is how the protein environment ensures that unproductive proton transfer from the retinal Schiff base to the nearby carboxylate counterion is avoided in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 98 publications
(164 reference statements)
2
38
0
Order By: Relevance
“…The QM method during the optimization was the CAM-B3LYP method [36]. For the MM part, the CHARMM36 protein force field [37,38] and the TIP3P water model [39] were employed throughout all our computations. The Amber [40] QM/MM interface [41] was used to generate final input files from the optimized structure.…”
Section: Structural Modellingmentioning
confidence: 99%
“…The QM method during the optimization was the CAM-B3LYP method [36]. For the MM part, the CHARMM36 protein force field [37,38] and the TIP3P water model [39] were employed throughout all our computations. The Amber [40] QM/MM interface [41] was used to generate final input files from the optimized structure.…”
Section: Structural Modellingmentioning
confidence: 99%
“…Computational methods, particularly molecular dynamics simulations and quantum mechanics simulations, play crucial roles in understanding the role of water in the structure and function of biomacromolecules. Molecular dynamics simulations were used to understand the role of water molecules in protein–DNA binding [ 183 ], enthalpy–entropy compensation during protein–ligand interactions [ 184 ], proton transfer reactions in channel rhodopsins [ 185 ], etc. Furthermore, MD simulations were used to complement experimental methods like terahertz absorption spectroscopy [ 186 ], neutron scattering [ 187 ], and time-resolved fluorescence spectroscopy [ 34 ] to understand the structure and dynamics of folded and intrinsically disordered proteins.…”
Section: Novel Insights From Computational Methodsmentioning
confidence: 99%
“…41 SCC-DFTB provides a good description of biological systems containing retinal [50][51][52] and has been utilized in the past to study the impact of the retinal active-site structure on absorption and IR spectra. [53][54][55] Here, we use four of the previously generated MD trajectories: 41 two with deprotonated E162 and two with protonated. All other amino acid residues are in their standard protonation states, except for E122, E129 and D195, which we model as neutral.…”
Section: Simulation Setupmentioning
confidence: 99%
“…Several studies have shown the Schiff base in ChR to be involved in hydrogen-bonding networks containing the counterions D292/E162 and water molecules. 33,41,[98][99] Because these interactions can contribute to the opsin shift and because SCC-DFTB is able to model hydrogen-bonding networks with the same quality as full DFT with a medium-sized basis set, 45 we investigated their effect by divding our snapshots into three hydrogen-bonding patterns: The Schiff base hydrogenbonding with water only (HBw) (Figure 4a), the Schiff base hydrogen-bonding with a counterion (HBc) (either D292 or E162, Figure 4b), or the Schiff base forming a three-center hydrogen bond with water and either D292 or E162 (HBwc, Figure 4c). Figure 5a).…”
Section: Hydrogen-bonding Partners Of the Schiff Basementioning
confidence: 99%
See 1 more Smart Citation